Assessment of dose to functional sub-structures in the lower urinary tract in locally advanced cervical cancer radiotherapy. (March 2019) - Spampinato, S.; Fokdal, L.; Marinovskij, E.; Axelsen, S.; Pedersen, E.M.; Pötter, R.; Lindegaard, J.C.; Tanderup, K.
Highlights: Current dose reporting in cervix IGBT does not fully describe the lower urinary tract. Trigone dose and ICRU bladder point dose are highly correlated. Hotspots are often located in the bladder dome outside/partly outside the trigone. The points introduced (IUO and PIBS-U) can be used as urethral dose surrogates. Dose reporting of bladder sub-structures may improve understanding of toxicity. Abstract: Purpose: To provide an analysis of dose distribution in sub-structures that could be responsible for urinary toxicity after Image-Guided Adaptive BrachyTherapy (IGABT) in Locally Advanced Cervical Cancer (LACC). Methods: 105 LACC patients treated with radiochemotherapy and IGABT were selected. Sub-structures (bladder wall, trigone, bladder neck, urethra) were contoured on IGABT-planning MRIs. D2cm3 and D0.1cm3, ICRU Bladder-Point (ICRU BP) and Posterior-Inferior Border of Symphysis points (PIBS, PIBS + 2 cm, PIBS − 2 cm) doses were extracted. Internal-Urethral-Ostium (IUO) and PIBS-Urethra (PIBS-U) points were defined as urethral dose surrogates. Finally, the Vaginal Reference Length (VRL) was extracted. Values were converted into total EBRT + BT equivalent dose in 2 Gy fractions using α/β = 3 and T1/2  = 1.5 h. Results: Median D2cm3 for bladder and trigone were 71.7[interquartile-range:66.5;74.1]Gy and 57.8[53.3;63.6]Gy, respectively, while median D0.1cm3 were 82.2[77.6;89.1]Gy and 70.7[62.0;76.7]Gy, respectively. Median ICRU BP dose was 63.7[56.5;70.5]Gy and correlated with trigone D2cm3 and D0.1cm3, while bladder and trigone D2cm3 had poor correlation (R 2  = 0.492), as well as D0.1cm3 (R 2  = 0.356). Bladder neck D0.1cm3 was always lower than trigone D0.1cm3 and higher than IUO. Correlation between PIBS + 2 cm and IUO was poor (R 2  = 0.273), while PIBS and PIBS-U were almost equal (R 2  = 0.990). VRL correlated with dose to bladder base. Conclusions: The study confirmed that ICRU BP and trigone doses correlate. Bladder D2cm3 is not representative of trigone dose because hotspots are often placed in the bladder dome. VRL is a good indicator for bladder base sparing. In addition to D2cm3 and D0.1cm3 for whole bladder, ICRU BP, trigone D2cm3 and D0.1cm3, IUO and PIBS are useful for lower urinary tract reporting.